2006
DOI: 10.1373/clinchem.2006.074302
|View full text |Cite
|
Sign up to set email alerts
|

Bound Homocysteine, Cysteine, and Cysteinylglycine Distribution between Albumin and Globulins

Abstract: Background: Major portions of homocysteine (Hcy), cysteine (Cys), cysteinylglycine (CysGly), and glutathione in serum are covalently bound to proteins via disulfides. Albumin has been considered the dominant binding protein. Methods:Pooled serum and plasma from healthy adults were fractionated into albumin and globulins by affinity columns. Content of Hcy, Cys, CysGly, and glutathione was determined for serum and plasma fractions and purified proteins by an HPLC method before and after incubation with excess C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 35 publications
(45 reference statements)
1
33
0
Order By: Relevance
“…Steric constraints might favor reactivity of smaller reactants such as Cys and Hcy vs. Cys-Gly, or unpaired Cys in other proteins. Our data agree with recent observations in which higher ratios of Hcy:Cys-Gly for albumin than globulins have been found [36]. This may reflect differences in the reactivity or accessibility of the unpaired Cys in albumin and globulins.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Steric constraints might favor reactivity of smaller reactants such as Cys and Hcy vs. Cys-Gly, or unpaired Cys in other proteins. Our data agree with recent observations in which higher ratios of Hcy:Cys-Gly for albumin than globulins have been found [36]. This may reflect differences in the reactivity or accessibility of the unpaired Cys in albumin and globulins.…”
Section: Discussionsupporting
confidence: 93%
“…We found that the relative quantity of Cys-Gly is higher in the apoprotein fraction than in plasma both in controls and CKD patients, thus confirming our previous data on the high affinity of apoB for Cys-Gly. On the contrary, it has been amply reported that albumin shows an elevated affinity principally for Cys and Hcy [15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36]. Unusually, the unpaired Cys34 of albumin have a p K a <6 [15].…”
Section: Discussionmentioning
confidence: 99%
“…It has an unusually low pK of about 5 that results in increased reactivity and rates of disulfide-bond formation and exchange with other sulfhydryl-containing compounds in plasma (57,74,75 ). Albumin can form disulfide-linked dimers, with 2 albumin monomers linked by cysteine-34 residues, or the cysteine sidechain can be oxidized to a sulfonic acid (57,76 ).…”
Section: Covalently Modified Forms Of Albuminmentioning
confidence: 99%
“…It is known that a significant amount of plasma cysteine is present in protein-bound forms such as those forming S-S bonds with cysteine residues in albumin and globulins. 22) The plasma samples in the present study were de-proteinized prior to measurement, so the amount in the proteinbound form can be neglected.…”
Section: Cys Concentrations In Plasma Of Rats After Oral Administratimentioning
confidence: 99%